2019
DOI: 10.1111/gwao.12344
|View full text |Cite
|
Sign up to set email alerts
|

More‐than‐human emotions: Multispecies emotional labour in the tourism industry

Abstract: The concept of emotional labour has been subject to critique, evaluation, development and extension over the last 35 years, but it remains firmly anthropocentric. This article begins to address this shortcoming by illustrating some of the productive potential of extending the concept of emotional labour to include more-than-human and multispecies perspectives.Organisations are not solely human phenomena, but research usually fails to consider the role of nonhumans in work in contemporary capitalism. Using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 86 publications
(77 reference statements)
0
32
0
2
Order By: Relevance
“…Equestrianism requires high levels of commitment, including time, emotion, and financial input, and so often becomes an important marker of individual and collective identity (Dashper, 2017;. Dashper (2019) argues that our leisure lives are often richer because of nonhuman animals, who play, relax, compete and work with and for us as a result of more-than-human encounters within a multispecies world. mETHod A multispecies ethnographic and posthumanistic approach was undertaken toward human-equine relational well-being within tourism.…”
Section: Human-horse Relations Within Tourism Landscapesmentioning
confidence: 99%
See 3 more Smart Citations
“…Equestrianism requires high levels of commitment, including time, emotion, and financial input, and so often becomes an important marker of individual and collective identity (Dashper, 2017;. Dashper (2019) argues that our leisure lives are often richer because of nonhuman animals, who play, relax, compete and work with and for us as a result of more-than-human encounters within a multispecies world. mETHod A multispecies ethnographic and posthumanistic approach was undertaken toward human-equine relational well-being within tourism.…”
Section: Human-horse Relations Within Tourism Landscapesmentioning
confidence: 99%
“…Previously human-animal relations have focused around human consumption and utilization of animals for peoples' benefit; however, more recently, authors such as those indicated above, as well as Fox (2006), Bertella (2014), Davis and Maurstad (2016), Danby et al (2019), Dashper (2019), Dashper and Brymer (2019) have began to realize the significance of animals in their own right, as sentient beings, worthy of moral consideration. The shifting role of the horse in society is acknowledged by Dashper (2012Dashper ( , 2017 and more recently by the works of Dashper and Brymer (2019) and Sturød et al (2019) indicating that once it was considered a vital partner to humans in terms of agriculture and warfare as well particularly with reference to transportation; however nowadays, the horse plays a predominant partner within sport, leisure, and tourism, and horses are becoming increasingly popular as companion and therapy animals (Wolframm et al, 2013).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing body of work that considers human-equine leisure, and although very different to that between humans and dogs, the relationship between humans and horses is also long, close and complex. Numerous equestrian practices could usefully be considered multispecies leisure, and research in this field covers multiple activities ranging from equestrian tourism (Buchmann, 2017;Dashper, 2019;Gilbert & Gillett, 2014;Sigurðardóttir & Helgadóttir, 2015) to competitive sport (Dashper, 2012;Gilbert & Gillett, 2012;Wipper, 2000) to non-competitive interactions and relationships (Dashper, 2017a;Hockenhull, Birke, & Creighton, 2010;Maurstad, Davis, & Cowles, 2013). Human-equine leisure practices and associated experiences can provide hedonistic activities and assist with the emergence and development of meaningful relationships.…”
Section: Leisure As a Multispecies Practicementioning
confidence: 99%